Gender equality in German universities: vernacularising the battle for the best brains - Kathrin S. Zippel; Myra Marx Ferree; Karin Zimmermann (Gender and Education, 2016)
We examine how global pressures for competitiveness and gender equality have merged into a discourse of `inclusive excellence' in the twenty-first century and shaped three recent German higher education programmes. After placing these programmes in the larger discourse about gender inequalities, we focus on how they adapt current global concerns about both being `the best' and increasing `gender equality' in locally specific ways, a process called vernacularisation. German equality advocates used `meeting international standards' as leverage, drew on self-governance norms among universities, used formal gender plans as mechanisms to direct change, and set up competition to legitimate intervention. This specific incremental policy path for increasing women's status in German universities also mobilised the national funding agency and local gender equality officers as key actors, and placed particular emphasis on family friendliness as the expression of organisational commitment to gender equality.
Additional information: Akzeptierte Manuskriptfassung (postprint) / Accepted version (postprint)
Keywords: 330; gender equality policy; Germany; science; academia; gender mainstreaming; globalisation